PERAN PEMERINTAH DALAM PERLINDUNGAN SOSIAL PENYANDANG DISABILITAS DI PEKANBARU (Studi pada organisasi perkumpulan kesejahteraan penyandang cacat) - Gustin Indah Pratiwi; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Is a person with disabilities or physical state of the biological system is different from other in general. Persons with disabilities is a group of people who have been marginalized and often discrimination in social and political life. This research on the government role in protection for people with disabilitiiesin pekanbaru (study on the organization welfare associations with disabilities). This research on the government role in social protection welfare associations with disabilities in pekanbaru include things about the government concern for disabled people is done though organization welfare associations with disabilities (PKPC). Organization welfare associations with disabilities is an organization or institution whose existence is expected to play an active role in the struggle for justice and welfare rights for people with disabilities as citizens as well as delete a variety of views and poor judgment against the disabled. To determine the role of government to the people with disabilities can be seen from the questionnaires distributed. Researchs to test the validity and realiability to 30 samples to determine wheter the question in the questionnaire can answer the problem of research. Researchers using spearman correlation analysis because the collected in the from ordinal data. The results of research know of the role of government against people with disabilities, although got as expected.Keyword: People With Disabilities, The Role Of Government, Organization Welfare Associations With Disabilities